Resin foam and foam member
The resin foam addresses the need for improved punching workability and reduced dust generation by controlling cell structure and surface characteristics, ensuring minimal thickness change and effective protection in narrow spaces.
Patent Information
- Application Number
- JP2024106389
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-05
- Filing Date
- 2024-07-01
- Publication Date
- 2025-01-20
AI Technical Summary
Existing foams used in electronic devices face challenges with narrow clearance requirements, necessitating improved punching workability and reduced dust generation, especially as devices become thinner and components smaller.
A resin foam with specific properties including a cell structure, low apparent density, controlled surface roughness, and a surface layer to enhance punching workability and suppress dust generation, achieved through precise control of cell structure and surface characteristics.
The resin foam exhibits minimal thickness change during punching, excellent workability, and reduced dust generation, ensuring effective protection and stability in narrow spaces.
Smart Images

Figure 2025010072000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin foam and a foam member. [Background technology]
[0002] Foams are often used as cushioning materials to protect the screens, circuit boards, and electronic components of electronic devices. In recent years, with the trend toward thinner electronic devices, there is a demand for narrower clearances in the areas where cushioning materials are placed. Furthermore, with the trend toward smaller electronic devices and more multifunctional devices, the electronic components used also tend to become smaller, which may require smaller cushioning materials (foams).
[0003] Usually, when a foamed body having a desired shape is obtained, a foam raw material is punched. In the punching process, a high pressure is applied to the foamed body using a die to obtain a foamed body having a desired shape. A foamed body to be applied to a place with a narrow clearance is required to have excellent punching processability, in other words, to have a small change in thickness due to punching.
[0004] Furthermore, in recent years, foams have become problematic in terms of dust generation during processing, partly due to the increasing complexity of processing shapes, and foams that are excellent in punching processability and low dust generation are therefore in demand. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP2017-186504A [Patent Document 2] JP2015-034299A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a resin foam that is excellent in punching processability and suppresses dust generation. [Means for solving the problem]
[0007] [1] A resin foam according to an embodiment of the present invention is a resin foam comprising a foam layer having a cell structure, the foam layer having an apparent density of 0.06 g / cm 3 or more, and the resin foam has an arithmetic mean surface roughness Ra of 50 μm or less. [2] In the resin foam according to the above [1], the foam layer may have an open cell ratio of 90% or less. [3] In the resin foam according to the above [1] or [2], the foam layer may have an average cell diameter of 300 μm or less. [4] In the resin foam according to any one of the above [1] to [3], the foam layer may have a coefficient of variation of cell diameter of 0.6 or less. [5] The resin foam according to any one of the above [1] to [4], wherein the resin foam is provided with a density of 1000 g / cm 2 The thickness recovery rate after maintaining the applied load for 120 seconds may be 80% or more. [6] The resin foam according to any one of [1] to [5] above may further include a surface layer on at least one side of the foam layer. [7] In the resin foam according to the above item [6], the surface layer may have a single layer thickness of 0.02 mm or more. [8] In the resin foam according to the above [6] or [7], the surface layer may have a total thickness of 5% or more of the thickness of the resin foam. [9] In the resin foam according to any one of the above [6] to [8], a ratio of the monolayer thickness of the surface layer to the foamed layer thickness (thickness of foamed layer / monolayer thickness of surface layer) may be 5-55.
[10] In the resin foam according to any one of [6] to [9] above, the surface layer may be a heat-fusible layer.
[11] In the resin foam according to any one of [1] to
[10] above, the foam layer may contain a polyolefin-based resin.
[12] In the resin foam according to the above item
[11] , the polyolefin-based resin may be a mixture of a polyolefin other than the polyolefin-based elastomer and a polyolefin-based elastomer.
[13] A foam member according to an embodiment of the present invention has the resin foam according to any one of [1] to
[12] above, and a pressure-sensitive adhesive layer disposed on at least one side of the resin foam. Effect of the Invention
[0008] According to the present invention, it is possible to provide a foam that has excellent punching workability, exhibits little change in thickness before and after punching, and suppresses dust generation during processing such as punching. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of a resin foam according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a foam member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A. Resin foam The resin foam according to the embodiment of the present invention has an arithmetic mean surface roughness Ra of at least one surface of 50 μm or less. The resin foam includes a foam layer. The foam layer has a bubble structure (cell structure). Examples of the bubble structure (cell structure) include a closed cell structure, an open cell structure, and a semi-open semi-closed cell structure (a cell structure in which a closed cell structure and an open cell structure are mixed). Preferably, the cell structure of the resin foam is a semi-open semi-closed cell structure. Typically, the resin foam of the present invention is obtained by foaming a resin composition. The resin composition is a composition containing at least a resin constituting the resin foam.
[0011] 1 is a schematic cross-sectional view of a resin foam according to one embodiment of the present invention. A resin foam 100 according to an embodiment of the present invention includes a foam layer 10 and a surface layer 20 formed on at least one surface of the foam layer. In one embodiment, the surface layer may be, for example, a heat-melting layer formed by heat-melting the foam layer.
[0012] The apparent density of the foam layer is 0.06 g / cm 3 Within such a range, a resin foam having excellent punching processability, flexibility, and stress dispersion properties can be obtained. In addition, a resin foam having reduced dust generation during punching can be obtained. The apparent density of the foam layer is preferably 0.065 g / cm 3 More preferably, it is 0.07 g / cm 3 More preferably, it is 0.075 g / cm 3 More preferably, it is 0.08 g / cm 3 If the density is within this range, the above-mentioned effects become significant. The apparent density of the foamed layer is preferably 0.4 g / cm 3 More preferably, it is 0.2 g / cm 3 More preferably, it is 0.1 g / cm or less. 3 The foaming property can be judged by the apparent density. The method for measuring the apparent density will be described later.
[0013] In one embodiment, the tensile strength of the resin foam is 0.5 MPa or more. Within this range, a resin foam excellent in maintaining its shape during punching can be obtained. Also, a resin foam in which dust generation during punching is suppressed can be obtained. The tensile strength of the resin foam is preferably 0.7 MPa or more, more preferably 1.0 MPa or more, even more preferably 1.2 MPa or more, and particularly preferably 1.3 MPa or more. Within this range, the above effects become significant. Also, the tensile strength of the resin foam is preferably 6 MPa or less, more preferably 3 MPa or less. The tensile strength can be measured by subjecting a dumbbell-shaped No. 1 sample defined in JIS K6251 4.1 to a tensile test in accordance with JIS K6767 (measurement temperature: 23°C, chuck distance: 10 mm, tensile speed: 500 mm / min).
[0014] In one embodiment, the 50% compression load of the resin foam is 20 N / cm 2 Within this range, a resin foam having favorable flexibility and excellent punching processability can be obtained. The 50% compression load of the resin foam is preferably 15 N / cm or less. 2 More preferably, it is 12 N / cm 2 or less, and more preferably 10 N / cm 2 or less, and more preferably 8 N / cm 2 or less, and particularly preferably 5 N / cm 2 or less, most preferably 3 N / cm 2 Within this range, the above-mentioned effects are remarkable. The lower limit of the 50% compressive load of the resin foam is, for example, 0.5 N / cm 2 The 50% compression load of a resin foam is the stress (N) when it is compressed to 50% of its compression ratio per unit area (1 cm 2 ) converted.
[0015] As described above, the resin foam has an arithmetic mean surface roughness Ra of at least one surface of 50 μm or less. If the range is within this range, a resin foam with suppressed dust generation can be obtained. The arithmetic mean surface roughness Ra of the resin foam is preferably 40 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, particularly preferably 10 μm or less, and most preferably 7 μm or less. If the range is within this range, the above effect becomes remarkable. In addition, the lower limit of the arithmetic mean surface roughness Ra of the surface layer is, for example, 1 μm. The arithmetic mean surface roughness Ra of the resin foam can be adjusted by the composition of the resin constituting the resin foam and the surface layer formation conditions (temperature, etc.) described later. The arithmetic mean surface roughness Ra can be measured in accordance with JIS B 0601 (1994).
[0016] In the embodiment of the present invention, by setting the apparent density of the foam layer within the above range (preferably, further setting the tensile strength and / or 50% compression load of the resin foam within the above range), a resin foam having favorable flexibility and excellent punchability can be obtained. More specifically, the resin foam exhibits favorable behavior in that the shape change such as thickness change is small even when punched, and recovers in a short time even when the thickness is temporarily reduced by punching, and has excellent punchability. The resin foam is advantageous in that it exhibits the above-mentioned excellent punchability even if it is configured to be thick. By using the above configuration and further setting the arithmetic mean surface roughness Ra of the resin foam within the above range, dust generation can be suppressed. In the embodiment of the present invention, it is particularly advantageous in that dust generation is suppressed even in a thick resin foam. For example, according to the resin foam according to the embodiment of the present invention, when the resin foam is temporarily fixed to an adhesive sheet and then peeled off, dust generation due to the destruction of the resin foam can be prevented. Examples of the adhesive sheet include a carrier sheet used for storing and transporting a resin foam, a foam member described later, and the like.
[0017] In one embodiment, the roughness of the surface layer is 50 μm or less in terms of arithmetic mean surface roughness Ra. By forming the surface layer, the arithmetic mean surface roughness Ra of the resin foam can be easily adjusted, and the dust generation suppression effect becomes significant. The arithmetic mean surface roughness Ra of the surface layer is preferably 40 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, particularly preferably 10 μm or less, and most preferably 7 μm or less. The lower limit of the arithmetic mean surface roughness Ra of the surface layer is, for example, 1 μm.
[0018] In one embodiment, the resin foam as described above can be formed by using a resin having a die swell ratio of 1.4 or less at a melting point (melting point of the resin constituting the resin foam) +20°C as the resin constituting the resin foam (foam layer). That is, in one embodiment, the die swell ratio of the resin forming the resin foam (foam layer) at a melting point +20°C before foaming is 1.4 or less. If a resin having a die swell ratio in the above range is used, shrinkage during the formation of the resin foam is prevented, and a thick resin foam (foam layer) can be formed, and the resin foam (foam layer) can contain small bubbles. The die swell ratio of the resin forming the resin foam (foam layer) at a melting point +20°C before foaming is preferably 1.2 or less, more preferably 1.1 or less. The lower limit of the die swell ratio of the resin (before foaming) is, for example, 1.05 (preferably 1.02, more preferably 1.01). In addition, the die swell ratio at melting point +20°C of the resin constituting the resin foam (i.e., the resin after foaming) is preferably 1.4 or less, more preferably 1.2 or less, and even more preferably 1.1 or less. The lower limit of the die swell ratio of the resin (after foaming) is, for example, 1.05 (preferably 1.02, more preferably 1.01). In this specification, the die swell ratio means a value obtained by dividing the diameter of the resin discharged from the die when the molten resin is discharged from the die by the diameter of the die. The die swell ratio is calculated by measuring the diameter of the obtained string-like molded product obtained by extruding the resin in a molten state at melting point +20°C using a die having a length of 10 mm and an aperture of 1 mmφ at a shear rate of 20 mm / s, and calculating the ratio by the formula: diameter of molded product (mm) / die aperture (mm). In addition, the melting point of the resin is measured by the peak top temperature of the endothermic peak obtained by differential scanning calorimetry (DSC) measurement. Differential scanning calorimetry (DSC) is measured using a differential scanning calorimeter (e.g., trade name "Q-2000", TA Instruments) under conditions of a sample weight of 3 mg and a heating rate of 10°C / min. When there are two or more peaks, the peak top temperature on the higher temperature side is regarded as the melting point.
[0019] In one embodiment, the resin foam (foam layer) as described above can be formed by using a resin having a shear viscosity of 3000 Pa·s or less at a melting point (melting point of the resin constituting the resin foam) + 20°C. That is, in one embodiment, the shear viscosity of the resin forming the resin foam (foam layer) at a melting point + 20°C before foaming is 3000 Pa·s or less. If a resin having a shear viscosity in the above range is used, the gas used for forming the cell structure during the formation of the resin foam can be preferably dispersed, and as a result, a foam layer with a small bubble size can be obtained. The shear viscosity of the resin forming the resin foam (foam layer) at a melting point + 20°C before foaming is preferably 2500 Pa·s or less, more preferably 2100 Pa·s or less, even more preferably 2000 Pa·s or less, and particularly preferably 1900 Pa·s or less. The lower limit of the shear viscosity of the resin (before foaming) is, for example, 500 Pa·s (preferably 700 Pa·s, more preferably 1000 Pa·s). The shear viscosity of the resin constituting the resin foam (i.e., the resin after foaming) at the melting point + 20°C is preferably 3000 Pa·s or less, more preferably 2500 Pa·s or less, even more preferably 2100 Pa·s or less, particularly preferably 2000 Pa·s or less, and most preferably 1900 Pa·s or less. The lower limit of the shear viscosity of the resin (after foaming) is, for example, 500 Pa·s (preferably 700 Pa·s, more preferably 1000 Pa·s). In this specification, the shear viscosity can be measured by extruding a resin in a molten state at the melting point + 20°C using a die with a length of 10 mm and an aperture of 1 mmφ at a shear rate of 20 mm / s.
[0020] The thickness of the resin foam is preferably 70 μm or more, more preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and particularly preferably 400 μm or more. The thickness of the resin foam is preferably 8000 μm or less, more preferably 4000 μm or less, even more preferably 3000 μm or less, and particularly preferably 2000 μm or less. If the thickness is within such a range, it is advantageous in that excellent punching workability and impact absorption properties can be exhibited.
[0021] The thickness of the foam layer is preferably 50 μm or more, more preferably 100 μm or more, even more preferably 150 μm or more, even more preferably 200 μm or more, and particularly preferably 250 μm or more. The thickness of the foam layer is preferably 7500 μm or less, more preferably 3500 μm or less, and even more preferably 1000 μm or less. If it is within such a range, it is advantageous in that a fine and uniform cell structure can be formed and excellent punching processability and impact absorption can be exhibited.
[0022] The cell density of the foam layer is preferably 30 cells / mm 2 More preferably, 50 pieces / mm 2 More preferably, 70 pieces / mm 2 More preferably, 80 pieces / mm 2 More preferably, 90 pieces / mm 2 More preferably, it is 100 pieces / mm 2 More preferably, the number is 110 / mm 2 That is all. If the density is within this range, the above-mentioned effects become more pronounced. Furthermore, the higher the cell density, the easier it is to store energy when compressed, and a resin foam with excellent compression recovery can be obtained. Such a resin foam has excellent punching processability. Furthermore, the cell density of the foam layer is preferably 400 cells / mm 2 More preferably, 200 / mm 2 More preferably, the number is 150 / mm 2or less, and particularly preferably 130 pieces / mm 2 The cell number density of the foam layer is the cell number density in a cross section observed in a randomly selected cross section of the foam layer, and can be determined by image analysis of the cross section of the foam layer.
[0023] The average bubble diameter (average cell diameter) in the foamed layer is preferably 300 μm or less, more preferably 250 μm or less, more preferably 200 μm or less, more preferably 180 μm or less, even more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 80 μm or less. The average bubble diameter (average cell diameter) is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more. Within such a range, a resin foam having excellent flexibility and stress dispersion can be obtained. In addition, a resin foam having excellent compression recovery, punching processability, and resistance to repeated impact can be obtained. The method for measuring the average bubble diameter will be described later.
[0024] The coefficient of variation of the bubble diameter (cell diameter) in the foam layer is preferably 0.6 or less, more preferably 0.55 or less, more preferably 0.50 or less, more preferably 0.45 or less, more preferably 0.40 or less, more preferably 0.30 or less, even more preferably 0.25 or less, and particularly preferably 0.20 or less. Within such a range, a resin foam having small variations in bubble deformation can be obtained when a compressive force is applied by punching or the like. With such a resin foam, for example, when punched, a processed product (cut product) having excellent thickness accuracy can be obtained. Furthermore, if the coefficient of variation of the bubble diameter is within the above range, deformation due to impact becomes uniform, local stress load is prevented, and a resin foam having excellent stress dispersion and particularly excellent impact resistance can be obtained. The smaller the coefficient of variation, the more preferable it is, and the lower limit thereof is, for example, 0.15 (preferably 0.1, more preferably 0.01). A method for measuring the coefficient of variation of the bubble diameter will be described later.
[0025] The foam layer has a foam ratio (cell ratio) of preferably 30% or more, more preferably 50% or more, and further preferably 80% or more. Within this range, a resin foam having appropriate flexibility can be obtained. Such a resin foam has excellent punching processability and prevents the occurrence of cut residues when punched. The upper limit of the foam ratio is, for example, 99% or less. The method for measuring the foam ratio will be described later.
[0026] The thickness of the bubble walls (cell walls) of the foam layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. The thickness of the bubble walls (cell walls) of the foam layer is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. Within this range, a resin foam having appropriate strength can be obtained. Such a resin foam has excellent punching processability, and is prevented from being torn, dusted, or left uncut during punching. Furthermore, if the thickness of the bubble walls is within the above range, a resin foam having excellent flexibility and stress dispersion can be obtained. The thickness of the bubble walls can be measured by capturing an enlarged image of the bubble part of the resin foam and analyzing the image using the analysis software of the measuring instrument.
[0027] When the foam layer has a semi-open, semi-closed cell structure, the proportion of the closed cell structure therein is preferably higher than 10% by volume, more preferably higher than 40% by volume. In this specification, the proportion of the closed cell structure in the foam layer is determined, for example, by immersing the measurement object in water in an environment of 23°C temperature and 50% humidity, measuring the mass thereafter, and then sufficiently drying in an oven at 80°C, and then measuring the mass again. In addition, since open cells can retain moisture, the mass of the open cells is measured and determined.
[0028] The open cell ratio of the foam layer is preferably 90% by volume or less, more preferably 70% by volume or less, and even more preferably 60% by volume or less. Within such a range, a resin foam with reduced dust generation can be obtained. Also, a resin foam with excellent punching processability can be obtained. Also, the open cell ratio of the foam layer is preferably 10% by volume or more, and more preferably 20% by volume or more.
[0029] The impact absorption of the resin foam is preferably 20% or more, more preferably 27% or more, even more preferably 30% or more, particularly preferably 35% or more, and most preferably 40% or more. The impact absorption is measured as follows. A test specimen was formed by placing a resin foam, double-sided tape (product number: No. 5603W, Nitto Denko), and PET film (product number: Diafoil MRF75, Mitsubishi Plastics) on top of the impact force sensor in that order. A 66g iron ball was dropped onto the test specimen from a height of 50cm above the PET film to measure the impact force F1. · Also, drop an iron ball directly onto the impact force sensor as described above to measure the impact force F0 of the blank. Calculate the shock absorption (%) from F1 and F0 using the formula (F0-F1) / F0×100.
[0030] The above resin foam is applied with a load of 1000g / cm 2 The thickness recovery rate after maintaining the load applied for 120 seconds is preferably 80% or more, more preferably 85% or more, more preferably 87% or more, even more preferably 90% or more, even more preferably 92% or more, and particularly preferably 95% or more. Within such a range, excellent punching workability is achieved. The higher the thickness recovery rate, the more preferable it is, and the upper limit is, for example, 99% (preferably 100%). The method for measuring the thickness recovery rate will be described later.
[0031] The thickness recovery rate after processing of the resin foam is preferably 80% or more, more preferably 85% or more, more preferably 87% or more, even more preferably 90% or more, even more preferably 92% or more, and particularly preferably 95% or more. Within such a range, the resin foam has excellent punching processability. The higher the thickness recovery rate after processing of the resin foam, the more preferable it is, and the upper limit is, for example, 99%. In this specification, the thickness recovery rate after processing of the resin foam is the thickness recovery rate calculated from the thickness of the end and the center of the punched piece when the resin foam is punched into a 10 mm square by the formula [100×(1-(center thickness-end thickness) / center thickness)].
[0032] The resin foam may have any suitable shape depending on the purpose, and a representative example of such a shape is a sheet.
[0033] As described above, in one embodiment, the surface layer may be a heat-melting layer formed by heat-melting the foam layer. A resin foam having a heat-melting layer may be obtained, for example, by rolling the foam layer (or a precursor of the foam layer (foam structure)) using a pair of heating rolls heated to a temperature equal to or higher than the melting temperature of the resin composition constituting the resin foam.
[0034] The single layer thickness of the surface layer is preferably 0.015 mm or more, more preferably 0.02 mm or more, more preferably 0.022 mm or more, and even more preferably 0.025 mm or more. Within such a range, a resin foam in which dust generation is particularly suppressed can be obtained. Furthermore, the single layer thickness of the surface layer is preferably 5 mm or less, more preferably 2 mm or less, even more preferably 1 mm or less, even more preferably 0.5 mm or less, and even more preferably 0.2 mm or less. Within such a range, a resin foam with excellent impact absorption properties can be obtained.
[0035] When the surface layer is formed on both sides of the foam layer, the total thickness of the surface layer is preferably 0.03 mm or more, more preferably 0.04 mm or more, more preferably 0.045 mm or more, and even more preferably 0.05 mm or more. Within such a range, a resin foam with particularly suppressed dust generation can be obtained. In addition, the total thickness of the surface layer is preferably 10 mm or less, more preferably 4 mm or less, even more preferably 2 mm or less, even more preferably 1 mm or less, and even more preferably 0.4 mm or less. Within such a range, a resin foam with excellent impact absorption can be obtained.
[0036] The ratio of the single layer thickness of the surface layer to the foam layer thickness (thickness of foam layer / single layer thickness of surface layer) is preferably 55 or less, more preferably 50 or less, even more preferably 45 or less, and even more preferably 40 or less. Within such a range, a resin foam having excellent impact absorption properties and excellent punching processability can be obtained. The ratio of the single layer thickness of the surface layer to the foam layer thickness (thickness of foam layer / single layer thickness of surface layer) is preferably 5 or more, more preferably 8 or more, even more preferably 10 or more, even more preferably 12 or more, even more preferably 15 or more, even more preferably 20 or more, even more preferably 22 or more, even more preferably 25 or more, and even more preferably 30 or more. Within such a range, a resin foam having particularly suppressed dust generation can be obtained.
[0037] The total thickness of the surface layer is preferably 5% or more, more preferably 8% or more, and even more preferably 9% or more, relative to the thickness of the resin foam. Within this range, a resin foam in which dust generation is particularly suppressed can be obtained. The total thickness of the surface layer is preferably 85% or less, more preferably 80% or less, even more preferably 70% or less, even more preferably 50% or less, even more preferably 30% or less, and even more preferably 20% or less, relative to the thickness of the resin foam. Within this range, a resin foam having excellent impact absorption properties and excellent punching processability can be obtained.
[0038] The average bubble diameter (average cell diameter) in the surface layer is preferably 80 μm or less, more preferably 50 μm or less, and further preferably 40 μm or less.
[0039] The ratio of the average bubble diameter (average cell diameter) of the foamed layer to the average bubble diameter (average cell diameter) of the surface layer (average bubble diameter of the foamed layer / average bubble diameter of the surface layer) is preferably 1.1 or more, more preferably 1.3 or more, even more preferably 1.5 or more, even more preferably 1.8 or more, even more preferably 2 or more, and even more preferably 2.5 or more. Within such a range, a resin foam in which dust generation is particularly suppressed can be obtained. The ratio of the average bubble diameter (average cell diameter) of the foamed layer to the average bubble diameter (average cell diameter) of the surface layer (average bubble diameter of the foamed layer / average bubble diameter of the surface layer) is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. Within such a range, a resin foam in which dust generation is particularly suppressed can be obtained. In addition, generally, the smaller the bubble diameter of the foamed layer, the more dust generation is suppressed. However, if the bubble diameter of the foamed layer is too small, the cell wall thickness becomes thin, and the interlayer strength of the foamed layer becomes weak, which may make it difficult to suppress dust generation. From this viewpoint, it is preferable that the size of the cell diameter is within the above-mentioned preferred range, and that the ratio of the cell diameter in the foamed layer to the cell diameter in the surface layer is within the above-mentioned specific range.
[0040] The air bubble ratio of the surface layer is preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, particularly preferably 5% or less, and most preferably 0. If it is within such a range, a resin foam in which dust generation is particularly suppressed can be obtained.
[0041] The ratio of the air void ratio of the surface layer to the air void ratio of the foamed layer (air void ratio of the surface layer / air void ratio of the foamed layer) is preferably 0.1 or less, more preferably 0.08 or less, and further preferably 0.05 or less. If it is within such a range, a resin foam in which dust generation is particularly suppressed can be obtained.
[0042] The ratio of the foamed layer to the surface layer (foamed layer / surface layer) is preferably 1.5 or more, more preferably 2.0 or more, more preferably 5 or more, more preferably 7 or more, even more preferably 10 or more, even more preferably 12.5 or more, even more preferably 15 or more, and even more preferably 20 or more. Within such a range, a resin foam with particularly suppressed dust generation can be obtained. The ratio of the foamed layer to the surface layer (foamed layer / surface layer) is preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. Within such a range, a resin foam with particularly suppressed dust generation can be obtained.
[0043] The resin foam can be formed by any suitable method as long as the effects of the present invention are not impaired. A representative example of such a method is a method of foaming a resin composition containing a resin material (polymer).
[0044] A-1. Resin composition The foam layer can be typically obtained by foaming a resin composition. The resin composition includes any appropriate resin material (polymer).
[0045] Examples of the polymer include acrylic resins, silicone resins, urethane resins, polyolefin resins, ester resins, rubber resins, etc. The polymers may be used alone or in combination of two or more.
[0046] The content of the polymer is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, further preferably 40 to 80 parts by weight, and particularly preferably 40 to 60 parts by weight, relative to 100 parts by weight of the resin composition. If the content is within such a range, a resin foam having superior flexibility and stress dispersion can be obtained.
[0047] In one embodiment, a polyolefin resin is used as the polymer.
[0048] The content of the polyolefin resin is preferably 50 parts by weight to 100 parts by weight, more preferably 70 parts by weight to 100 parts by weight, even more preferably 90 parts by weight to 100 parts by weight, particularly preferably 95 parts by weight to 100 parts by weight, and most preferably 100 parts by weight, relative to 100 parts by weight of the above polymer.
[0049] The polyolefin resin is preferably at least one selected from the group consisting of polyolefins and polyolefin elastomers, and more preferably, polyolefins and polyolefin elastomers are used in combination. The polyolefins and polyolefin elastomers may each be used alone or in combination of two or more. In this specification, the term "polyolefin" does not include "polyolefin elastomers".
[0050] When polyolefin and polyolefin elastomer are used in combination as the polyolefin resin, the weight ratio of polyolefin to polyolefin elastomer (polyolefin / polyolefin elastomer) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, further preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30. In one embodiment, the weight ratio of polyolefin to polyolefin elastomer (polyolefin / polyolefin elastomer) is preferably 25 / 75 to 75 / 25, more preferably 35 / 65 to 65 / 35. Within such a range, a resin foam can be obtained that has excellent compression recovery, suppresses shape changes (particularly thickness changes) before and after punching during punching, has appropriate strength, and is excellent in punching processability.
[0051] As the polyolefin, any suitable polyolefin may be adopted within a range that does not impair the effects of the present invention. Examples of such polyolefin include linear polyolefins and branched (branched) polyolefins. In one embodiment, a branched polyolefin is used as the polyolefin-based resin. In this embodiment, only a branched polyolefin may be used as the polyolefin, or a branched polyolefin and a linear polyolefin may be used in combination. By using a branched polyolefin, a resin foam having a small average cell diameter and excellent impact resistance can be obtained. The content of the branched polyolefin is preferably 30 parts by weight to 100 parts by weight, more preferably 50 parts by weight to 80 parts by weight, based on 100 parts by weight of the polyolefin.
[0052] The polyolefin may be, for example, a polymer containing a structural unit derived from an α-olefin. The polyolefin may be composed of only a structural unit derived from an α-olefin, or may be composed of a structural unit derived from an α-olefin and a structural unit derived from a monomer other than an α-olefin. When the polyolefin is a copolymer, any suitable copolymerization form may be adopted as the copolymerization form. For example, a random copolymer, a block copolymer, etc. may be mentioned.
[0053] The α-olefin that can constitute the polyolefin is preferably, for example, an α-olefin having 2 to 8 carbon atoms (preferably 2 to 6, more preferably 2 to 4) (e.g., ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, etc.). Only one type of α-olefin may be used, or two or more types of α-olefins may be used.
[0054] Examples of monomers other than α-olefins constituting polyolefins include ethylenically unsaturated monomers such as vinyl acetate, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, vinyl alcohol, etc. The monomers other than α-olefins may be of only one type or of two or more types.
[0055] Specific examples of polyolefins include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene (propylene homopolymer), copolymers of ethylene and propylene, copolymers of ethylene and an α-olefin other than ethylene, copolymers of propylene and an α-olefin other than propylene, copolymers of ethylene, propylene and an α-olefin other than ethylene and propylene, and copolymers of propylene and an ethylenically unsaturated monomer.
[0056] In one embodiment, a polypropylene-based polymer having a propylene-derived structural unit is used as the polyolefin. Examples of the polypropylene-based polymer include polypropylene (propylene homopolymer), a copolymer of ethylene and propylene, and a copolymer of propylene and an α-olefin other than propylene, and preferably polypropylene (propylene homopolymer). The polypropylene-based polymer may be used alone or in combination of two or more kinds.
[0057] The melt flow rate (MFR) of the polyolefin at a temperature of 230°C is preferably 0.25g / 10 min to 10g / 10 min, more preferably 0.3g / 10 min to 6g / 10 min, even more preferably 0.35g / 10 min to 5g / 10 min, particularly preferably 0.35g / 10 min to 1g / 10 min, and most preferably 0.35g / 10 min to 0.6g / 10 min, in order to further exhibit the effects of the present invention. In this specification, the melt flow rate (MFR) refers to the MFR measured at a temperature of 230°C and a load of 2.16 kgf (21.2 N) based on ISO1133 (JIS-K-7210). In one embodiment, the die swell ratio and shear viscosity of the resin are controlled by the melt flow rate of the polyolefin constituting the resin foam.
[0058] The weight average molecular weight of the polyolefin is preferably 50,000 to 120,000, more preferably 55,000 to 110,000, and further preferably 60,000 to 100,000. Within such ranges, the die swell ratio and shear viscosity of the resin can be preferably adjusted. Furthermore, the molecular weight distribution (weight average molecular weight / number average molecular weight) of the polyolefin is preferably 7 to 10, more preferably 6 to 9. Within such ranges, the die swell ratio and shear viscosity of the resin can be preferably adjusted. The weight average molecular weight and number average molecular weight can be determined by gel permeation chromatography measurement (solvent: tetrahydrofuran, polystyrene equivalent).
[0059] As the polyolefin, commercially available products may be used, such as "E110G" (manufactured by Prime Polymer Co., Ltd.), "EA9" (manufactured by Japan Polypropylene Corporation), "EA9FT" (manufactured by Japan Polypropylene Corporation), "E-185G" (manufactured by Prime Polymer Co., Ltd.), "WB140HMS" (manufactured by Borealis), and "WB135HMS" (manufactured by Borealis).
[0060] As the polyolefin-based elastomer, any suitable polyolefin-based elastomer may be adopted within the scope of not impairing the effects of the present invention. Examples of such polyolefin-based elastomers include so-called non-crosslinked thermoplastic olefin-based elastomers (TPOs) such as ethylene-propylene copolymers, ethylene-propylene-diene copolymers, ethylene-vinyl acetate copolymers, polybutene, polyisobutylene, chlorinated polyethylene, elastomers in which a polyolefin component and a rubber component are physically dispersed, and elastomers in which a polyolefin component and a rubber component have a microphase separation structure; dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) which are multiphase polymers obtained by dynamically heat treating a mixture containing a resin component A (olefin-based resin component A) forming a matrix and a rubber component B forming a domain in the presence of a crosslinking agent, and which have a sea-island structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in the resin component A which is a matrix (sea phase); and the like.
[0061] The polyolefin-based elastomer preferably contains a rubber component. Examples of such rubber components include those described in JP-A-08-302111, JP-A-2010-241934, JP-A-2008-024882, JP-A-2000-007858, JP-A-2006-052277, JP-A-2012-072306, JP-A-2012-057068, JP-A-2010-241897, JP-A-2009-067969, and JP-A-03 / 002654.
[0062] Specific examples of elastomers having a microphase-separated structure of a polyolefin component and an olefin-based rubber component include elastomers made of polypropylene resin (PP) and ethylene-propylene rubber (EPM), elastomers made of polypropylene resin (PP) and ethylene-propylene-diene rubber (EPDM), etc. The weight ratio of the polyolefin component to the olefin-based rubber component (polyolefin component / olefin-based rubber) is preferably 90 / 10 to 10 / 90, more preferably 80 / 20 to 20 / 80.
[0063] Dynamically crosslinked thermoplastic olefin elastomers (TPV) generally have a higher elastic modulus and smaller compression set than non-crosslinked thermoplastic olefin elastomers (TPO), which gives them good recovery properties and allows them to show excellent recovery properties when made into resin foams.
[0064] As described above, dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) are obtained by dynamically heat treating a mixture containing a resin component A (olefin-based resin component A) that forms a matrix and a rubber component B that forms domains, in the presence of a crosslinking agent. These TPVs are multiphase polymers having an island-sea structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in resin component A, which is the matrix (sea phase).
[0065] Examples of dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) include those described in JP-A-2000-007858, JP-A-2006-052277, JP-A-2012-072306, JP-A-2012-057068, JP-A-2010-241897, JP-A-2009-067969, and JP-A-03 / 002654.
[0066] As the dynamically crosslinked thermoplastic olefin-based elastomer (TPV), commercially available products may be used, such as "Zeotherm" (manufactured by Zeon Corporation), "Thermorun" (manufactured by Mitsubishi Chemical Corporation), and "Sarlink 3245D" (manufactured by Toyobo Co., Ltd.).
[0067] The polyolefin elastomer preferably has a melt flow rate (MFR) of 1.5 g / 10 min to 25 g / 10 min, more preferably 2 g / 10 min to 20 g / 10 min, and further preferably 2 g / 10 min to 15 g / 10 min at a temperature of 230° C. In one embodiment, the die swell ratio and shear viscosity of the resin are controlled by the melt flow rate of the polyolefin elastomer constituting the foamed layer.
[0068] In one embodiment, two or more polyolefin-based elastomers having different melt flow rates (MFR) at 230° C. within the above range are used in combination. In this case, a polyolefin-based elastomer (low MFR polyolefin-based elastomer) having a melt flow rate (MFR) at 230° C. of preferably 1.5 g / 10 min or more and less than 8 g / 10 min (more preferably 2 g / 10 min to 5 g / 10 min) can be used in combination with a polyolefin-based elastomer (high MFR polyolefin-based elastomer) having a melt flow rate (MFR) at 230° C. of preferably 8 g / 10 min to 25 g / 10 min (more preferably 9 g / 10 min to 20 g / 10 min, and even more preferably 10 g / 10 min to 20 g / 10 min). In this way, the melt tension of the polyolefin-based elastomer is preferably adjusted, and as a result, the effects of the present invention become remarkable.
[0069] The blending ratio of the low MFR polyolefin elastomer to the high MFR polyolefin elastomer (low MFR polyolefin elastomer / high MFR polyolefin elastomer; weight ratio) is preferably 1.5 to 5, more preferably 1.8 to 3.5, and particularly preferably 2 to 3. Within such a range, the melt tension of the polyolefin elastomer can be preferably adjusted, and as a result, the effects of the present invention become remarkable.
[0070] The melt tension of the polyolefin elastomer (at 190°C at break) is preferably less than 10 cN, more preferably 5 cN to 9.5 cN. In one embodiment, the die swell ratio and shear viscosity of the resin are controlled by the melt tension of the polyolefin elastomer constituting the foamed layer.
[0071] The JIS A hardness of the polyolefin elastomer is preferably 30° to 95°, more preferably 35° to 90°, further preferably 40° to 88°, particularly preferably 45° to 85°, and most preferably 50° to 83°. The JIS A hardness is measured based on ISO7619 (JIS K6253).
[0072] In one embodiment, the foam layer (i.e., the resin composition) may further include a filler. By including a filler, a foam layer that requires a large amount of energy to deform the cell walls can be formed, and the foam layer exhibits excellent impact absorption properties. In addition, by including a filler, a fine and uniform cell structure can be formed, which is advantageous in that excellent impact absorption properties can be exhibited. Only one type of filler may be used alone, or two or more types may be used in combination.
[0073] The content of the filler is preferably 10 to 150 parts by weight, more preferably 30 to 130 parts by weight, and further preferably 50 to 100 parts by weight, relative to 100 parts by weight of the polymer constituting the foamed layer. If the content is within such a range, the above-mentioned effects become prominent.
[0074] In one embodiment, the filler is an inorganic material. Examples of materials constituting the inorganic filler include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, silicon nitride, boron nitride, crystalline silica, amorphous silica, metal (e.g., gold, silver, copper, aluminum, nickel), carbon, graphite, etc.
[0075] In one embodiment, the filler is an organic material. Examples of materials constituting the organic filler include polymethylmethacrylate (PMMA), polyimide, polyamideimide, polyetheretherketone, polyetherimide, and polyesterimide.
[0076] A flame retardant may be used as the filler. Examples of the flame retardant include bromine-based flame retardants, chlorine-based flame retardants, phosphorus-based flame retardants, and antimony-based flame retardants. From the viewpoint of safety, a non-halogen, non-antimony-based flame retardant is preferably used.
[0077] Examples of non-halogen, non-antimony flame retardants include compounds containing aluminum, magnesium, calcium, nickel, cobalt, tin, zinc, copper, iron, titanium, boron, etc. Examples of such compounds (inorganic compounds) include hydrated metal compounds such as aluminum hydroxide, magnesium hydroxide, magnesium oxide-nickel oxide hydrate, and magnesium oxide-zinc oxide hydrate.
[0078] The filler may be subjected to any suitable surface treatment, such as a silane coupling treatment or a stearic acid treatment.
[0079] The bulk density of the filler is preferably 0.8 g / cm 3 More preferably, it is 0.6 g / cm or less. 3or less, and more preferably 0.4 g / cm 3 or less, and particularly preferably 0.3 g / cm 3 Within this range, the filler can be contained with good dispersibility, and the effect of adding the filler can be fully exhibited even with a small filler content. A foamed layer with a small filler content is advantageous in that it is highly foamed, flexible, and has excellent stress dispersion and appearance. The lower limit of the bulk density of the filler is, for example, 0.01 g / cm. 3 and preferably 0.05 g / cm 3 and more preferably 0.1 g / cm 3 It is.
[0080] The number average particle diameter (primary particle diameter) of the filler is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. Within such a range, the filler can be contained with good dispersibility and a uniform cell structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The lower limit of the number average particle diameter of the filler is, for example, 0.1 μm. The number average particle diameter of the filler can be measured using a particle size distribution meter (MicrtracII, Microtrack Bell Co., Ltd.) using a suspension prepared by mixing 1 g of filler in 100 g of water as a sample.
[0081] The specific surface area of the filler is preferably 2 m 2 / g or more, more preferably 4m 2 / g or more, more preferably 6m 2 / g or more. If the filler is in this range, the filler can be incorporated with good dispersibility and a uniform cell structure can be formed. As a result, a resin foam excellent in stress dispersion and appearance can be obtained. The upper limit of the specific surface area of the filler is, for example, 20 m 2 The specific surface area of the packing material can be measured by the BET method, that is, by adsorbing a molecule with a known adsorption area onto the packing material surface at a low temperature using liquid nitrogen, and measuring the amount of the molecule adsorbed.
[0082] The resin composition may contain any other appropriate components as long as the effects of the present invention are not impaired. Such other components may be one type only, or two or more types. Examples of such other components include rubber, resins other than the polymers blended as the resin material, softeners, aliphatic compounds, antiaging agents, antioxidants, light stabilizers, weathering agents, UV absorbers, dispersants, plasticizers, carbon, antistatic agents, surfactants, crosslinking agents, thickeners, rust inhibitors, silicone compounds, tension modifiers, shrinkage inhibitors, flow modifiers, gelling agents, curing agents, reinforcing agents, foaming agents, foam nucleating agents, colorants (pigments, dyes, etc.), pH adjusters, solvents (organic solvents), thermal polymerization initiators, photopolymerization initiators, lubricants, crystal nucleating agents, crystallization accelerators, vulcanizing agents, surface treatment agents, and dispersion aids.
[0083] A-2. Formation of resin foam The resin foam of the present invention is typically obtained by foaming a resin composition. The resin foam having a surface layer can be obtained by forming a surface layer on a foam layer (or a precursor of the foam layer (foam structure)) obtained by foaming a resin composition by any appropriate method. As the foaming method (a method for forming bubbles), a method usually used in foam molding, such as a physical method or a chemical method, can be adopted. That is, the resin foam may typically be a foam formed by foaming using a physical method (physical foam), or a foam formed by foaming using a chemical method (chemical foam). The physical method is generally a method in which a gas component such as air or nitrogen is dispersed in a polymer solution and bubbles are formed by mechanical mixing (mechanical foam). The chemical method is generally a method in which cells are formed by gas generated by thermal decomposition of a foaming agent added to a polymer base, to obtain a foam.
[0084] The resin composition to be subjected to foam molding may be prepared, for example, by mixing the components using any appropriate melt kneading device, such as an open-type mixing roll, a non-open-type Banbury mixer, a single-screw extruder, a twin-screw extruder, a continuous kneader, or a pressure kneader.
[0085] <Embodiment 1 for forming a resin foam (foam layer)> An example of one embodiment 1 for forming a resin foam (foam layer) is a form in which a resin foam (foam layer) is formed through a step (step A) of mechanically foaming an emulsion resin composition (emulsion containing a resin material (polymer) etc.). Examples of foaming devices include high-speed shear devices, vibration devices, and pressurized gas discharge devices. Among these foaming devices, high-speed shear devices are preferred from the viewpoints of miniaturizing the bubble diameter and producing a large volume. This one embodiment 1 for forming a resin foam (foam layer) is applicable to formation from any resin composition.
[0086] From the viewpoint of film-forming properties, the solids concentration of the emulsion is preferably high. The solids concentration of the emulsion is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 50% by weight or more.
[0087] The bubbles generated by mechanical stirring are gases that have been taken into the emulsion. Any suitable gas may be used as the gas as long as it is inert to the emulsion and does not impair the effects of the present invention. Examples of such gases include air, nitrogen, and carbon dioxide.
[0088] The emulsion resin composition foamed by the above method (bubble-containing emulsion resin composition) is applied onto a substrate and dried (step B), to obtain a resin foam (foam layer). Examples of the substrate include a release-treated plastic film (a release-treated polyethylene terephthalate film, etc.), a plastic film (a polyethylene terephthalate film, etc.), etc.
[0089] In step B, any appropriate method may be adopted as the coating method and drying method as long as the effects of the present invention are not impaired. Step B preferably includes a preliminary drying step B1 in which the bubble-containing emulsion resin composition applied to the substrate is dried at 50° C. or higher and lower than 125° C., and a main drying step B2 in which the composition is further dried at 125° C. or higher and 200° C. or lower.
[0090] By providing the preliminary drying step B1 and the main drying step B2, it is possible to prevent the coalescence of bubbles and the bursting of bubbles due to a sudden rise in temperature. In particular, in a foamed sheet having a small thickness, the coalescence and bursting of bubbles due to a sudden rise in temperature is likely to occur, so providing the preliminary drying step B1 is very significant. The temperature in the preliminary drying step B1 is preferably 50°C to 100°C. The time for the preliminary drying step B1 is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes. The temperature in the main drying step B2 is preferably 130°C to 180°C or less, more preferably 130°C to 160°C. The time for the main drying step B2 is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.
[0091] <Embodiment 2 in which a resin foam (foam layer) is formed> In one embodiment 2 of forming a resin foam (foam layer), a foam is formed by foaming a resin composition with a foaming agent. As the foaming agent, a foaming agent usually used for foam molding can be used, and from the viewpoint of environmental protection and low pollution to the foamed object, it is preferable to use a high-pressure inert gas.
[0092] As the inert gas, any suitable inert gas may be adopted as long as it is inert to the resin composition and can be impregnated. Examples of such inert gas include carbon dioxide, nitrogen gas, and air. These gases may be used in combination. Among these, carbon dioxide is preferred from the viewpoint of a large amount of impregnation into the resin material (polymer) and a fast impregnation speed.
[0093] The inert gas is preferably in a supercritical state. That is, it is particularly preferable to use carbon dioxide in a supercritical state. In a supercritical state, the solubility of the inert gas in the resin composition is increased, making it possible to mix the inert gas at a high concentration, and the inert gas becomes highly concentrated when the pressure is suddenly lowered, so that more bubble nuclei are generated, and the density of the bubbles formed by the growth of the bubble nuclei is larger than in other states even if the porosity is the same, so that fine bubbles can be obtained. The critical temperature of carbon dioxide is 31°C, and the critical pressure is 7.4 MPa.
[0094] Examples of the method for forming a foam by impregnating a resin composition with a high-pressure inert gas include a gas impregnation step in which an inert gas is impregnated under high pressure into a resin composition containing a resin material (polymer), a depressurization step in which the pressure is reduced after the gas impregnation step to foam the resin material (polymer), and a heating step in which bubbles are grown by heating as necessary. In this case, a previously molded unfoamed molded body may be impregnated with an inert gas, or a molten resin composition may be impregnated with an inert gas under pressure and then molded during depressurization. These steps may be performed by either a batch method or a continuous method. That is, the resin composition may be molded into an appropriate shape such as a sheet to form an unfoamed resin molded body, and then the unfoamed resin molded body is impregnated with a high-pressure gas and foamed by releasing the pressure, or the resin composition may be kneaded with a high-pressure gas under pressure, and molded and foamed at the same time by releasing the pressure.
[0095] An example of producing a foam by the batch method is shown below. For example, a resin sheet for foam molding is produced by extruding a resin composition using an extruder such as a single screw extruder or a twin screw extruder. Alternatively, the resin composition is uniformly kneaded using a kneader equipped with blades such as a roller, a cam, a kneader, or a Banbury type, and pressed to a predetermined thickness using a hot plate press or the like to produce an unfoamed resin molded body. The unfoamed resin molded body thus obtained is placed in a high-pressure container, and high-pressure inert gas (such as carbon dioxide in a supercritical state) is injected to impregnate the unfoamed resin molded body with the inert gas. When the inert gas is sufficiently impregnated, the pressure is released (usually to atmospheric pressure), and bubble nuclei are generated in the resin. The bubble nuclei may be allowed to grow at room temperature as they are, or may be allowed to grow by heating in some cases. As a heating method, known or commonly used methods such as a water bath, an oil bath, a heated roll, a hot air oven, far infrared rays, near infrared rays, and microwaves can be used. After the bubbles are grown in this manner, the foam can be obtained by rapidly cooling the foam with cold water or the like to fix the shape. The unfoamed resin molded product to be foamed is not limited to a sheet-like product, and various shapes can be used depending on the application. The unfoamed resin molded product to be foamed can be produced by other molding methods such as extrusion molding, press molding, and injection molding.
[0096] An example of producing a foam by a continuous method is shown below. For example, a resin composition is kneaded using an extruder such as a single-screw extruder or a twin-screw extruder while injecting (introducing) a high-pressure gas (particularly an inert gas, or further carbon dioxide) to sufficiently impregnate the resin composition with the high-pressure gas in a kneading impregnation step, and the resin composition is extruded through a die or the like provided at the tip of the extruder to release the pressure (usually to atmospheric pressure), and foaming and foaming are simultaneously performed in a molding decompression step to form the foam. In addition, when foaming in a continuous method, a heating step for growing bubbles by heating may be provided as necessary. After the bubbles are grown in this way, the shape may be fixed by rapidly cooling with cold water or the like as necessary. The high-pressure gas may be introduced continuously or discontinuously. In addition, in the kneading impregnation step and the molding decompression step, for example, an extruder or an injection molding machine may be used. In addition, as a method of heating when growing bubble nuclei, any appropriate method such as a water bath, an oil bath, a heat roll, a hot air oven, far infrared rays, near infrared rays, and microwaves may be used. The foam may have any suitable shape, such as a sheet, a prismatic shape, a cylindrical shape, or an irregular shape.
[0097] The amount of gas mixed when foam molding the resin composition is preferably 2% by weight to 10% by weight, more preferably 2.5% by weight to 8% by weight, and even more preferably 3% by weight to 6% by weight, based on the total amount of the resin composition, in order to obtain a highly foamed resin foam (foam layer).
[0098] The pressure when the resin composition is impregnated with the inert gas can be appropriately selected in consideration of operability and the like. For example, such a pressure is preferably 6 MPa or more (for example, 6 MPa to 100 MPa), and more preferably 8 MPa or more (for example, 8 MPa to 50 MPa). In addition, the pressure when carbon dioxide in a supercritical state is used is preferably 7.4 MPa or more from the viewpoint of maintaining the supercritical state of carbon dioxide. If the pressure is lower than 6 MPa, the bubble growth during foaming is remarkable, and the bubble diameter becomes too large, so that a preferable average cell diameter (average bubble diameter) may not be obtained. This is because, when the pressure is low, the amount of gas impregnated is relatively small compared to that at high pressure, and the bubble nucleation rate decreases and the number of bubble nuclei formed decreases, so that the amount of gas per bubble increases conversely and the bubble diameter becomes extremely large. In addition, in a pressure range lower than 6 MPa, the bubble diameter and bubble density change significantly even with a small change in the impregnation pressure, so that it is easy to make it difficult to control the bubble diameter and bubble density.
[0099] The temperature in the gas impregnation step varies depending on the type of inert gas used and the type of components in the resin composition, and can be selected from a wide range. In consideration of operability, the temperature is preferably 10°C to 350°C. The impregnation temperature when impregnating an inert gas into an unfoamed molded body is preferably 10°C to 250°C, more preferably 40°C to 230°C, in the batch process. In addition, the impregnation temperature when extruding a molten polymer impregnated with a gas to simultaneously perform foaming and molding is preferably 60°C to 350°C in the continuous process. When carbon dioxide is used as the inert gas, the temperature during impregnation is preferably 32°C or higher, more preferably 40°C or higher, in order to maintain a supercritical state.
[0100] In the depressurizing step, the depressurizing speed is preferably 5 MPa / sec to 300 MPa / sec in order to obtain uniform fine bubbles.
[0101] The heating temperature in the heating step is preferably 40°C to 250°C, and more preferably 60°C to 250°C.
[0102] In one embodiment, after obtaining a foamed structure through a predetermined process (e.g., after obtaining a foamed layer by the method of <Embodiment 1> or <Embodiment 2>), the foamed structure is rolled to obtain a resin foam having a surface layer. The foamed structure may be thinned before the roll rolling. By going through such a process, a resin foam having an appropriately adjusted aspect ratio can be obtained. Also, a resin foam having a small thickness (e.g., 0.2 mm or less) can be obtained. The surface layer (thermally fusible layer) can also be formed by the roll rolling.
[0103] The foam structure can be thinned using any appropriate slicer. The thickness of the foam structure after thinning is preferably 0.18 mm to 1 mm, more preferably 0.2 mm to 0.8 mm, and further preferably 0.3 mm to 0.7 mm.
[0104] Preferably, the roll used in the rolling is a heated roll. The temperature of the roll is preferably 150° C. to 250° C., more preferably 160° C. to 230° C. Within such a range, a resin foam having a preferred surface layer can be obtained.
[0105] The rolling ratio of the foamed structure (thickness after rolling / thickness before rolling×100) is preferably 80% or less, more preferably 10% to 80%, further preferably 20% to 75%, and particularly preferably 30% to 75%. If it is within such a range, a resin foam having a preferable surface layer formed thereon can be obtained.
[0106] B. Foam material 2 is a schematic cross-sectional view of a foam member according to one embodiment. The foam member 200 has a resin foam 100 and a pressure-sensitive adhesive layer 110 disposed on at least one side of the resin foam 100.
[0107] The thickness of the adhesive layer is preferably 5 μm or more, more preferably 6 μm or more, even more preferably 7 μm or more, and particularly preferably 8 μm or more. The thickness of the adhesive layer is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and most preferably 50 μm or less. When the thickness of the adhesive layer is within the above range, the foam material of the present invention can exhibit excellent impact absorption properties.
[0108] The adhesive layer may be a layer made of any suitable adhesive. Examples of the adhesive constituting the adhesive layer include rubber-based adhesives (synthetic rubber-based adhesives, natural rubber-based adhesives, etc.), urethane-based adhesives, acrylic urethane-based adhesives, acrylic-based adhesives, silicone-based adhesives, polyester-based adhesives, polyamide-based adhesives, epoxy-based adhesives, vinyl alkyl ether-based adhesives, fluorine-based adhesives, and rubber-based adhesives. The adhesive constituting the adhesive layer is preferably at least one selected from acrylic-based adhesives, silicone-based adhesives, and rubber-based adhesives. Such adhesives may be of only one type or of two or more types. The adhesive layer may be of one layer or of two or more layers.
[0109] When classified according to the adhesive form, examples of the adhesive include emulsion type adhesives, solvent type adhesives, ultraviolet cross-linking type (UV cross-linking type) adhesives, electron beam cross-linking type (EB cross-linking type) adhesives, hot melt type adhesives, etc. Such adhesives may be of only one type or of two or more types.
[0110] The water vapor permeability of the adhesive layer is preferably 50 (g / (m 2 24 hours) or less, and more preferably 30 (g / (m 2 24 hours) or less, and more preferably 20 (g / (m 2 24 hours) or less, and particularly preferably 10 (g / (m 2If the water vapor permeability of the pressure-sensitive adhesive layer is within the above range, the foam sheet can stabilize the impact absorption properties without being affected by moisture. The water vapor permeability can be measured, for example, by a method according to JIS Z 0208 under test conditions of 40°C and a relative humidity of 92%.
[0111] The adhesive constituting the adhesive layer may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of other components include other polymer components, softeners, antiaging agents, curing agents, plasticizers, fillers, antioxidants, thermal polymerization initiators, photopolymerization initiators, UV absorbers, light stabilizers, colorants (pigments, dyes, etc.), solvents (organic solvents), surfactants (e.g., ionic surfactants, silicone surfactants, fluorine surfactants, etc.), crosslinking agents (e.g., polyisocyanate crosslinking agents, silicone crosslinking agents, epoxy crosslinking agents, alkyl etherified melamine crosslinking agents, etc.). The thermal polymerization initiator and the photopolymerization initiator may be included in the material for forming the polymer component.
[0112] The foam member can be produced by any appropriate method, such as a method of laminating a resin foam and a pressure-sensitive adhesive layer, or a method of laminating a material for forming a pressure-sensitive adhesive layer and a resin foam and then forming a pressure-sensitive adhesive layer by a curing reaction or the like. EXAMPLES
[0113] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.
[0114] <Evaluation method> (1) Apparent density The density (apparent density) of the foam layer was calculated as follows. The foam layer of the resin foam obtained in the Examples and Comparative Examples was punched out to a size of 20 mm x 20 mm to prepare a test piece, and the dimensions of the test piece were measured with a vernier caliper. Next, the weight of the test piece was measured with an electronic balance. Then, the density was calculated according to the following formula. Apparent density (g / cm 3 ) = weight of test piece / volume of test piece
[0115] (2) 50% compression load The measurement was performed according to the method for measuring the compression hardness of resin foam described in JIS K 6767. Specifically, the resin foam obtained in the examples and comparative examples was cut into a size of 30 mm × 30 mm to prepare a test piece, and the stress (N) when compressed to a compression rate of 50% at a compression speed of 10 mm / min was measured per unit area (1 cm 2 ) per 50% compression load (N / cm 2 ) was decided.
[0116] (3) Average bubble size (average cell size) and coefficient of variation of bubble size (cell size) The resin foam was cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction). A digital microscope (product name "VHX-500", manufactured by Keyence Corporation) was used as a measuring instrument to capture an image of the cut surface of the resin foam. The image was analyzed using the analysis software of the measuring instrument to determine the number-average bubble diameter (average cell diameter) (μm) of the foam layer and surface layer. The number of bubbles in the captured enlarged image was about 400. The standard deviation was calculated from all the cell diameter data, and the coefficient of variation was calculated using the following formula. Coefficient of variation = standard deviation / average bubble size (average cell size)
[0117] (4) Air bubble rate (cell rate) The resin foam was cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction), and observed with a digital microscope (product name "VHX-500", manufactured by Keyence Corporation) as a measuring instrument. The image was binarized using image processing software (Mitani Shoji Co., Ltd., WinROOF), and the bubble ratio (bubble area ratio) of the foam layer and surface layer was calculated using the following formula. The number of bubbles in the enlarged image was about 400. Pore ratio (pore area ratio) (%) = pore area / total area
[0118] (5) Open cell ratio The foam layer was submerged in water in an environment of 23°C temperature and 50% humidity, and the weight was then measured, and the layer was thoroughly dried in an oven at 80°C and then the weight was measured again. The volume of the open cells was calculated from the water content obtained by the weight measurement, and further, the volume ratio of the open cells to the volume of the foam layer (open cell ratio) was calculated.
[0119] (6) Recovery rate of resin foam after processing (punching processability) The resin foam was punched in the MD direction (flow direction) and TD direction (direction perpendicular to the flow direction) using a mold (two cutting blades (product name "NCA07", thickness 0.7 mm, cutting edge angle 43°, spacing between the two cutting blades 10 mm, manufactured by Nakayama Corporation)) to a size of 10 mm x 10 mm, and the cross section in the MD direction and TD direction with the larger thickness change was observed with a microscope (product name "VHX-2000", manufactured by Keyence Corporation), and the thickness of the end and center were measured from the image. The measured thickness was used to calculate the thickness recovery rate after processing using the following formula. The larger the thickness recovery rate, the smaller the shape change due to punching and the better the punching processability. Post-processing thickness recovery rate (%) = 100 x (1-(center thickness-edge thickness) / center thickness)
[0120] (7) Thickness recovery rate (instantaneous recovery rate) Resin foam, 1000g / cm 2The load was applied and maintained for 120 seconds, the compression was released, and the thickness of the resin foam 0.5 seconds after the release (thickness 0.5 seconds after the compressed state was released) was measured. The thickness recovery rate (instantaneous recovery rate) was calculated from the "thickness 0.5 seconds after the compressed state was released" and the thickness of the resin foam before the load was applied (initial thickness) according to the following formula. Thickness recovery rate (%) = {(thickness 0.5 seconds after releasing the compression state) / (initial thickness)} x 100
[0121] (8) Carrier tape pick-up ability A resin foam (width: 10 mm × length: 120 mm) was stored for 24 hours or more under an atmosphere of temperature: 23±2°C and humidity: 50±5RH% (pretreatment conditions conforming to JIS Z 0237), and then fixed to a silicone-treated release paper using a double-sided adhesive tape (product name "No. 5603", manufactured by Nitto Denko Corporation, double-sided adhesive tape with substrate, substrate: PET substrate) with a width of 10 mm × length of 120 mm, and pressed with a 2 kg roller once back and forth so that the opposite side of the foam was in contact with the adhesive layer surface of a low-adhesive carrier tape (product name "3164S", manufactured by Kern Co., Ltd.), and left for 24 hours to prepare a measurement sample. If the carrier tape of the above measurement sample can be lifted by hand, the pick-up ability is If the carrier tape was peeled off and could not be lifted, the pickup property was evaluated as unsatisfactory (×).
[0122] (9) Carrier tape processability A resin foam (width: 10 mm × length: 120 mm) was stored for 24 hours or more under an atmosphere of temperature: 23±2°C and humidity: 50±5RH% (pretreatment conditions conforming to JIS Z 0237), and then fixed to a SUS plate using a double-sided adhesive tape (product name "No. 5603", manufactured by Nitto Denko Corporation) with a width of 10 mm × length of 120 mm, and pressed with a 2 kg roller once back and forth so that the opposite side of the resin foam was in contact with the adhesive layer surface of a weak adhesive carrier tape (product name "3165S", manufactured by Kern Instruments), and left for 24 hours to prepare a measurement sample. The carrier tape was quickly peeled off by hand, and the state of peeling was visually confirmed to evaluate whether or not surface damage had occurred to the foam. In Table 1, when there was no surface damage to the resin foam, it was marked as "pass" and when there was surface damage to the resin foam, it was marked as "fail." In addition, when there was no surface damage to the resin foam in the above evaluation and it was rated as "○," and when there was no damage to the foam layer of the resin foam when measured in the same manner as above using a strong adhesive carrier tape (product name "3166S," manufactured by Kern Co., Ltd.), it was marked as "pass" (◎).
[0123] (10) Arithmetic mean surface roughness Ra The arithmetic mean roughness Ra of the resin foam was measured in accordance with JIS B 0601 (1994) under the following measurement conditions. Measurement equipment: Confocal laser microscope (model: LEXT OLS5000, manufactured by Olympus) Settings: High accuracy settings Objective lens: 10x Evaluation length: 1279μm Filter: Gaussian filter Cutoff: λc=80.000μm, λs=none, λf=none
[0124] (11) Tensile strength The resin foam is molded into a dumbbell shape No. 1 as specified in JIS K6251 4.1. This was used as a sample, and the tensile strength in the TD direction was measured at a measurement temperature of 23° C. in accordance with JIS K6767.
[0125] Example 1 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 335 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 43 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure a was obtained. The foamed structure a was then cut into a thin film using a slicer, and a foamed structure a1 having a thickness of 1.0 mm was obtained. Furthermore, the foamed structure a1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 210° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0126] Example 2 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 335 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 45 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 15 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure b was obtained. The foamed structure b was then cut into a thin film using a slicer, and a foamed structure b1 with a thickness of 1.0 mm was obtained. Furthermore, the foamed structure b1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 210° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0127] Example 3 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 345 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 35 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 15 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure c was obtained. The foamed structure c was then cut into a thin film using a slicer, and a foamed structure c1 with a thickness of 1.0 mm was obtained. Furthermore, the foamed structure c1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 220° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0128] Example 4 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 345 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 40 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure d was obtained. The foamed structure d was then cut into a thin film using a slicer, and a foamed structure d1 having a thickness of 1.0 mm was obtained. Furthermore, the foamed structure d1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 220° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0129] Example 5 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 340 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 38 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure e was obtained. The foamed structure e was then cut into a thin film using a slicer, and a foamed structure e1 with a thickness of 1.0 mm was obtained. Furthermore, the foamed structure e1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 230° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0130] Example 6 A foamed structure e1 having a thickness of 1.0 mm was obtained in the same manner as in Example 5, except that carbon dioxide gas was injected in an amount of 4.6 parts by weight per 100 parts by weight of the resin. Furthermore, the foamed structure e1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 230° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0131] Example 7 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 3 40 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 38 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 3.8 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure f was obtained. The foamed structure f was then cut into a thin film using a slicer, and a foamed structure f1 with a thickness of 1.0 mm was obtained. Furthermore, the foamed structure f1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 230° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0132] Example 8 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm3 45 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 40 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure g was obtained. The foamed structure g was then cut into a thin film using a slicer, and a foamed structure g1 having a thickness of 1.0 mm was obtained. Furthermore, the foamed structure g1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 210° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0133] Example 9 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 345 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64,500, molecular weight distribution: 8.43), 35 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "9020NS", MFR: 14 g / 10 min (230°C, load 21.2 N)), 15 parts by weight of polyolefin elastomer (manufactured by Mitsui Chemicals, Inc., product name "4010NA", MFR: 5 g / 10 min (230°C, load 21.2 N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.2 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the resin was cooled to a temperature suitable for foaming, and a sheet-like foamed structure h was obtained. The foamed structure h was then cut into a thin film using a slicer, and a foamed structure h1 having a thickness of 1.0 mm was obtained. Furthermore, the foamed structure h1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 220° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0134] Comparative Example 1 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 340 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64500, molecular weight distribution: 8.43), 39 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14g / 10 min (230°C, load 21.2N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5g / 10 min (230°C, load 21.2N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foamed structure g was obtained. The foamed structure g was then cut into a thin film using a slicer, and a foamed structure g1 with a thickness of 0.8 mm was obtained. Furthermore, the foamed structure g1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 230° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0135] Comparative Example 2 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 340 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64500, molecular weight distribution: 8.43), 39 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14g / 10 min (230°C, load 21.2N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5g / 10 min (230°C, load 21.2N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.4 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the resin was cooled to a temperature suitable for foaming, and a sheet-like foamed structure h was obtained. The foamed structure h was then cut into a thin film using a slicer, and a foamed structure h1 with a thickness of 0.7 mm was obtained. Furthermore, the foamed structure h1 was passed through the gap between a pair of rolls (the gap between the rolls) heated to 230° C. to obtain a resin foam having a thickness of 0.6 mm. The gap between the rolls was set so that the thickness of the surface layer was the value shown in Table 1. In this way, a resin foam consisting of a surface layer / foam layer / surface layer was obtained.
[0136] Comparative Example 3 Polypropylene (propylene homopolymer, MFR: 0.4g / 10min (230℃, load 21.2N), density: 0.90g / cm 340 parts by weight of propylene glycol ether (ethylene content: 0% by weight, propylene content: 100% by weight, weight average molecular weight: 64500, molecular weight distribution: 8.43), 39 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "9020NS", MFR: 14g / 10 min (230°C, load 21.2N)), 17 parts by weight of polyolefin elastomer (Mitsui Chemicals, Inc., product name "4010NA", MFR: 5g / 10 min (230°C, load 21.2N)), 10 parts by weight of magnesium hydroxide (product name "KISUMA 5P", Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (product name "Asahi #35", Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into a strand shape, cooled with water, and formed into a pellet shape. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.4 parts by weight per 100 parts by weight of resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and a sheet-like foam structure i was obtained. The foam structure i was then cut into a thin film using a slicer, and a foam structure (foam layer) i1 with a thickness of 0.6 mm was obtained.
[0137] [Table 1] [Industrial Applicability]
[0138] The resin foam of the present invention can be suitably used, for example, as a cushioning material for electronic devices. [Explanation of symbols]
[0139] 10 Foam layer 20 Surface layer 100 Resin foam 110 Adhesive layer 200 Foam material
Claims
1. A resin foam comprising a foam layer having a cell structure, The apparent density of the foam layer is 0.06 g / cm 3 That's all. The resin foam has an arithmetic average surface roughness Ra of 50 μm or less. Resin foam.
2. The resin foam according to claim 1 , wherein the foam layer has an open cell rate of 90% or less.
3. The resin foam according to claim 1 , wherein the foam layer has an average cell diameter of 300 μm or less.
4. The resin foam according to claim 1 , wherein the foam layer has a coefficient of variation of cell diameter of 0.6 or less.
5. The resin foam has a weight per unit area of 1000 g / cm 2 The resin foam according to claim 1, having a thickness recovery rate of 80% or more after maintaining a load of 1.0 mm for 120 seconds.
6. The resin foam according to claim 1 , further comprising a surface layer on at least one side of the foam layer.
7. The resin foam according to claim 6 , wherein the surface layer has a single layer thickness of 0.02 mm or more.
8. The resin foam according to claim 6 , wherein the surface layer has a total thickness of 5% or more of a thickness of the resin foam.
9. The resin foam according to claim 6, wherein a ratio of the single layer thickness of the surface layer to the foam layer thickness (thickness of foam layer / single layer thickness of surface layer) is 5 to 55.
10. The resin foam according to claim 6 , wherein the surface layer is a heat-fusible layer.
11. The resin foam according to claim 1 , wherein the foam layer comprises a polyolefin-based resin.
12. The resin foam according to claim 11 , wherein the polyolefin-based resin is a mixture of a polyolefin other than the polyolefin-based elastomer and a polyolefin-based elastomer.
13. A pressure-sensitive adhesive sheet comprising the resin foam according to claim 1 and a pressure-sensitive adhesive layer disposed on at least one side of the resin foam. Foam material.
Citation Information
Patent Citations
Impact absorption material
JP2015034299A
Foam for buffer material and buffer material
JP2017186504A